2021
DOI: 10.1111/asj.13553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hay with or without concentrate or pellets on growth performance and meat quality of Ujimqin lambs on the Inner Mongolian Plateau

Abstract: This study aimed to evaluate growth performance and meat quality of Ujimqin lambs fed native grass hay without or with concentrate (HC) or pellets. Ninety non-castrated 6-month-old male lambs of good health and similar body weight (26.83 ± 0.26 kg) were randomly divided into three groups (five lambs per cage). The average daily gain and intake of the pellets and HC groups were significantly greater (p < .05) than those in the hay group. The carcass weight, net meat mass, loin eye area, and backfat thickness we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The meat quality of cattle is shown in Table 3 . The loin eye area is a useful measure of muscle growth and carcass meat content since it is closely related to carcass weight ( 29 ). In our study, feeding R1 resulted in a smaller ( p = 0.001) loin eye area compared to that of the control and R2 groups ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The meat quality of cattle is shown in Table 3 . The loin eye area is a useful measure of muscle growth and carcass meat content since it is closely related to carcass weight ( 29 ). In our study, feeding R1 resulted in a smaller ( p = 0.001) loin eye area compared to that of the control and R2 groups ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cooked meat rate was calculated according to the percentage difference in weight between pre- and post-cooked meat samples ( Needham et al, 2019 ). The fatty acids methyl esters were measured according to the AOAC (2005) and Bu et al (2021) methods with a gas chromatography–mass spectrometer 7890B (Agilent, California, United States).…”
Section: Methodsmentioning
confidence: 99%
“…But the native grass hay is used as feed for ruminants alone resulting in an imbalance between supply and demand of energy because of the lower nutrient and harsh weather in winter. Previous studies have demonstrated that supplementary with concentrate could improve growth performance and carcass characteristics ( Du et al, 2020 ; Bu et al, 2021 ). In addition, the pelleted diet-fed lambs could also improve the growth performance and carcass characteristics by enhancing dry matter (DM) and energy intake, which shake off the disadvantages of feeding native grass directly ( Du et al, 2020 ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Native grassland is widely distributed in the Mongolian Plateau and could provide sufficient nutrition for ruminants. Traditionally, grazing was the most common feeding system, but in recent years, the native grass hay (bales) have partially or totally replaced grazing for the ruminants in the Mongolian Plateau [4]. Ensiling is a traditional way of animal feed and green forage preservation because it can provide green forages for animals year-round, prolonging the storage time and effectively decreasing the nutrition lost in Microorganisms 2022, 10, 1154 2 of 12 forages [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the moisture content, the water-soluble carbohydrate content, and the numbers of epiphytic lactic acid bacteria microflora were lower than the requirement, making it difficult to produce silage with high quality [5]. Native grass hay has become the main feeding system in Inner Mongolia Plateau [4].…”
Section: Introductionmentioning
confidence: 99%